Chromosomal Microarray vs. NIPS: Analysis of 5541 Low-Risk Pregnancies. Issue 4 (April 2020) - Sagi-Dain, Lena; Vig, Lital Cohen; Kahana, Sarit; Yacobson, Shiri; Tenne, Tamar; Agmon-Fishman, Ifat; Klein, Cochava; Matar, Reut; Basel-Salmon, Lina; Maya, Idit
Abstract : (Abstracted from Genet Med 2019;21:2462–2467) Prenatal genetic testing is conducted today using a variety of methods: noninvasive prenatal screening (NIPS) and invasive prenatal testing with karyotyping and/or chromosomal microarray analysis (CMA). While NIPS can detect some genetic aberrations without an invasive procedure, karyotyping and CMA require amniocentesis or chorionic villi sampling.